Differentially Expressed Circular RNA Profile Signatures Identified in Prolificacy Trait of Yunshang Black Goat Ovary at Estrus Cycle - Liu, Yufang; Zhou, Zuyang; He, Xiaoyun; Jiang, Yanting; Ouyang, Yina; Hong, Qionghua; Chu, Mingxing (Frontiers in Physiology, 2022)
CircRNA acting as miRNA sponges play important roles in the growth process of animal individuals. Prolificacy trait of goats involved in many pathways, however, the variation of the circRNAs expression profiles in the different phases of estrus cycle at high and low yielding groups are still unknown. Here, we analysis the profile of circRNAs among high and low yielding groups in follicular phase (HF vs. LF), high and low yielding groups in luteal phase (HL vs. LL), and high and low yielding in whole estrus cycle (HF vs. HL and LF vs. LL) were detected using RNA-seq. A total of 283 (114 up-regulated and 169 down-regulated), 559 (299 up-regulated and 260 down-regulated), 449 (254 up-regulated and 195 down regulated) and 314 (210 up-regulated and 104 down-regulated) DE circRNAs were screened in HF vs. LF, HF vs. HL, HL vs. LL, and LF vs. LL groups, respectively. Enrichment analysis suggested that the target genes of DE circRNAs were mainly enriched in Oocyte meiosis, GnRH signaling pathway, and Estrogen signaling pathway. Integrate our previous study of miRNA-seq, there were 56 miRNAs could target to 192 DE circRNAs, including miR-133 family (miR-133a-3p and miR-133b), miR-129-3p and miR-21, which also had important influence on prolificacy trait of goats. Then, 18 circRNAs with coding potential was obtained by four software predictions, and 9 circRNAs were validation by qPCR. Together, circRNAs plays the key role in the prolificacy trait and the transform the follicular phase to the luteal phase in the estrus cycle of goats.